GE_GERICHTE C/23299/2013 vom 23. April 2015 - GE Cour de justice (2015)
DIVORCE; OBLIGATION D'ENTRETIEN; LIQUIDATION DU RÉGIME MATRIMONIAL | CPC.317.1; CC.125.1; CC.197.2; CC.204; CC.208; CC.209; CC.211